KAJIAN BUDAYA PADA ARSITEKTUR RUMAH TRADISIONAL JOGLO BUCU DI KABUPATEN PONOROGO - Hilba Yoga Pratama; Agung Budi Sardjono (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2023)
The traditional houses of each region in Indonesia are a distinctive symbol of the culture that exists in that area. One of these unique symbols is the traditional house in Ponorogo Regency, namely Joglo Bucu. Cultural values ​​are depicted in buildings, ornaments, spatial planning, spatial functions, building structures, and ritual ceremonies in the construction procession. Not only does the physical form of each element of the traditional building display beauty but it is bound to the values ​​of Javanese culture that prevail in society. Cultural values ​​become social capital to bring out the identity, characteristics, and uniqueness of the area. The research method used is descriptive qualitative, collecting data through field observations, interviews with homeowners and workers in the Joglo Bucu development procession, and related literature studies. This study aims to explain the culture and customs of the Javanese people in the construction procession, aesthetic ornaments, cultural symbols, and the cosmological relationship between humans, nature, and God. The results of this study provide an exexplainof each character closely related to Javanese culture and customs. The construction procession ritual involves stages carried out by Javanese customary rules, such as looking for days according to Javanese primbon calculations and determining the direction of the building, ceremonies, or rituals. The architectural form of Joglo Bucu has a meaning related to Javanese cosmology. The room layout and placement of ornaments in Joglo Bucu are based on balance and harmony, reflecting beliefs about the relationship between humans and the universe. Decorations on Joglo Bucu have symbols that reflect beauty, strength, and prosperity. To provide a deep understanding of the cultural values ​​ in the Joglo Bucu traditional house in Ponorogo Regency.